Inteligencia colectiva, metacognición y cultura digital. Nuevos horizontes de la Pedagogía contemporánea - Fabrizio Manuel Sirignano; Stefania Maddalena (Firenze University Press, 2019)
By highlighting how their pedagogical employment can promote a more active role of individuals in their learning process, this essay reflects on the importance of new technologies within education curricula. The paper argues that the adequate use of digital technologies'potential can foster peculiar cognitive, matecognitive and social abilities, and consequently yield a number of positive learning outcomes.